Determinants of the economy in multistrata agroforestry in Ethiopia - Waldén, Pirjetta; Eronen, Mari; Kaseva, Janne; Negash, Mesele; Kahiluoto, Helena (Elsevier, 2024)
Agroforestry represents a potentially multi-beneficial approach to land management as it may enhance a farming household’s income and income stability simultaneously with nutrition security and climate change mitigation. However, our comprehension of the specific characteristics within agroforestry systems that bolster economic productivity remains limited, exacerbating the challenges of land management for smallholder livelihoods. This complexity is compounded by the potential influence of carbon revenue, adding an additional layer of intricacy to the equation. This paper aimed to identify the key economic determinants of multistrata agroforestry in sub-Saharan Africa with and without potential carbon revenue. A quantitative survey of 135 farmers was performed regarding their multistrata agroforestry systems with contrasting histories in three regions of Ethiopia. The carbon sequestration rate and carbon stocks in agroforestry were assessed on one-fifth (27) of the farms. The relative importance of hypothetical determinants of agroforestry systems’ economic performance was modeled using descriptive statistics and generalized linear models. Farm size and fertilizer usage were the primary drivers of the farm economy, but farm net income was also highly influenced by the richness and diversity of the income sources. In addition, tree diversity had a positive impact on the net income, whereas the proportion of legume trees and trees with a large diameter correlated negatively with the income. Potential carbon revenue at prices of US$40 tCO2−1 and US$100 tCO2−1 increased income for multistrata agroforestry farms without significantly changing the magnitude of the identified key determinants. This suggests that the most economically viable agroforestry systems inherently possess a strong capacity for carbon sequestration, effectively serving as carbon sinks. Consequently, carbon revenue serves as a compelling financial incentive for the adoption of these agroforestry systems. Ultimately, this research underscores the pivotal role of biological and product diversity in shaping economic productivity within multistrata agroforestry systems. Moreover, it highlights the accessibility of diversity management for smallholder farmers, even under conditions of resource constraints.
Keywords: agroforestry; farm income; carbon revenue; Sub-Saharan Africa; diversification; land management